Iron oxide nanotube film formed on carbon steel for photoelectrochemical water splitting: effect of annealing temperature. (29th April 2016) - Deng, Hongda; Huang, Mao‐Chia; Weng, Wei‐Heng; Lin, Jing‐Chie
Abstract : Carbon steels (CSs) were anodized in an ethylene glycol solution containing 3 vol.% H2 O and 0.1 m NH4 F to coat with nanotube arrays film. The as anodized nanotube arrays film were annealed in argon atmosphere at various temperatures ranging from 250 to 550 °C for 4 h. The morphology and crystal phases of the film developed after annealing processes were examined using field emission scanning electron microscopy, X‐ray diffraction. Morphology transforms from nanobube arrays to nanotube bundles at 250 °C, to nanobube bundles with nanoflakes at 350 and 450 °C, to nanotube bundles with nanobelts at 550 °C. Amorphous transformed completely into maghemite at 350 °C and hematite with minor magnetite at 450 and 550 °C. Diffuse reflectance ultraviolet and visible spectra revealed iron oxide nanotube film annealed at 350 °C, or higher than 350 °C behaved tremendous absorbance ability in visible spectra range. Mott–Schottky analysis and linear scan voltammetry were performed in 1 m NaOH to show that iron oxide nanotube film annealed at 450 °C exhibited best charge carrier transfer ability upon illumination and superior photoelectrochemical properties compared with the films annealed at other temperatures. The film annealed at 450 °C displayed the photocurrent density of 0.13 mA cm −2 at 0.2 VAg/AgCl, but the film annealed at other temperatures with the photocurrent densities of lower than 0.05 mA cm −2 at 0.2 VAg/AgCl . The morphology and phase transform of iron oxide nanotube film at different annealing temperature results in the change of their photoelectrochemical properties. Copyright © 2016 John Wiley & Sons, Ltd.